Business Cycle Duration Dependence: A Parametric Approach - Sichel, Daniel E. (The Review of Economics and Statistics, 1991)
This paper reexamines duration dependence in U.S. business cycles using parametric hazard models. Positive duration dependence would indicate that expansions or contractions are more likely to end as they become older. This paper provides statistically significant evidence of positive duration dependence for expansions before World War II and contractions after World War II. The evidence is stronger than in earlier research utilizing nonparametric techniques, because certain nonparametric techniques have low statistical power against the type of duration dependence found in this paper. Evidence is also presented suggesting that expansions became longer, on average, after World War II, while contractions became shorter. Copyright 1991 by MIT Press.